Pengamatan Sosiologis tentang Perceraian di Aceh - Muhammad Sahlan (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Divorce cases in Aceh post conflict and disaster is increasing significantly.  Among the generating factors are conflict and Tsunami, the change of family  system, and the growth of inhabitants and modernisation. The lack of knowledge  and consciousness about foster home are not the roots or main factors contributing  to the increasing trend. But it is more to autonomy economically, education,  maturity and adult emotionally, and capability in keeping relationship with  kinship and extended family. Therefore, cross-sectoral cooperation in government  and community are required to decrease the divorce trend in Aceh.